PENERAPAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI KPK DAN FPB - Irna Cahyanti; Nurdin Muhamad; Fajar Nugraha (Cahaya Smart Nusantara, 2025)
Mathematics is often perceived as difficult and boring, leading to suboptimal learning outcomes. One key factor influencing student’s success in mathematics is emotional intelligence. This study aims to examine the significant differences in learning outcomes intelligences-based approach. This research employs a quantitative approach using an experimental one group pretest-posttest design. The subjects are fifth-grade students at elementary school 3 Cihurip. The intruments used include an emotional intelligence questionnaire and a learning outcome test. The questionnaire measures five indicators of emotional intelligence base on Daniel Goleman’s theory: self-awareness, self-regulation, motivation, empathy, and social skills. Survey results indicate that student’s emotional intelligence levels fall within the moderate category, with motivation and self-regulation contributing the most to learning success. These findings align with Goleman’s theory, which emphasizes the crucial role of emotional intelligence in academic achievement. The pretest posttest analysis reveals a significant improvement in learning outcomes, with a p-value of 0,000 < 0,05. Additionally, the N-Gain analysis shows an increase of 0,35 classified as a moderate improvement. This suggests that applying emotional intelligence contributes to student’s cognitive, affective, and social development. Thus, integrating emotional intelligence into mathematics learning can be an effective strategy to enhance academic performance while fostering student’s emotional and social skills.